Pengaruh Struktur Modal Terhadap Harga Saham dengan Kinerja Perusahaan sebagai Variabel Intervening pada Perusahaan Property dan Real Estate - Pilipus Ramandei; Ester Saranga; Jerry Sawai; Inka Josephine Abba (Universitas Yapis Papua, 2023)
This study aims to examine the direct effect of capital structure on company performance and stock prices; direct effect of company performance on stock prices. As well as testing the indirect effect of capital structure on stock prices through company performance. Hypothesis testing is carried out using the Partial Least Square (PLS) approach. The sample used consisted of 40 property and real estate companies listed on the Indonesia Stock Exchange from 62 companies, for 2018-2020. Sampling was done by purposive sampling method. The results of this research show that capital structure has no effect on stock prices. Stock prices tend to be more influenced by the demand and supply of shares by capital market participants. This shows that it is likely that investors who will invest in property and real estate companies in the form of shares will consider other information about the company besides information about the company's capital structure. While the capital structure does not affect the performance of the company's performance. These results indicate that changes in the company's capital structure caused by an increase in the amount of company debt do not improve company performance. However, the company's performance has a positive effect on stock prices. Meanwhile, capital structure has no effect on stock prices through company performance. These results indicate that the company's performance is not able to mediate the relationship between capital structure and stock prices